1991
DOI: 10.1063/1.349732
|View full text |Cite
|
Sign up to set email alerts
|

Structural properties of polycrystalline silicon films prepared at low temperature by plasma chemical vapor deposition

Abstract: Evolution with thickness of the structure of the polycrystalline silicon (poly-Si) films prepared at 300 °C has been studied by plasma decomposition of SiF4/SiH4/H2 source gases. The poly-Si films with varied thickness are characterized mainly by Raman spectroscopy, x-ray diffraction (XRD), and supplementarily by reflection high-energy electron diffraction, transmission electron microscopy, Fourier-transform infrared (FT-IR) spectroscopy, electron-spin resonance (ESR), and secondary-ion-mass spectroscopy (SIMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(43 citation statements)
references
References 26 publications
0
43
0
Order By: Relevance
“…23 Different energy densities result in different grain sizes, which further complicates the analysis, since the absorption coefficient changes too. 24 ␥ has been calculated to be between 0.8 and 0.9, the most widely used value being 0.8 for mixed phase silicon, especially for excimer laser crystallized silicon. 23,25,26 For this analysis too, ␥ was taken to be 0.8.…”
Section: A Raman Spectroscopymentioning
confidence: 99%
“…23 Different energy densities result in different grain sizes, which further complicates the analysis, since the absorption coefficient changes too. 24 ␥ has been calculated to be between 0.8 and 0.9, the most widely used value being 0.8 for mixed phase silicon, especially for excimer laser crystallized silicon. 23,25,26 For this analysis too, ␥ was taken to be 0.8.…”
Section: A Raman Spectroscopymentioning
confidence: 99%
“…They have found that the (1 1 0) orientation occurs at high H 2 pressure and Si 3 H 8 flow rate at T d below 560°C, but turn to (1 0 0) above T d of 575°C [24]. Kakinuma et al [25] have investigated the structural properties of poly-Si thin films with different thickness deposited at T d of 300°C by PECVD method using SiH 4 -SiF 4 -H 2 gas mixture. They have found that the grains are strongly (1 1 0) oriented in good agreement with the present work.…”
Section: Resultsmentioning
confidence: 97%
“…Regarding the mechanism of the crystalline growth in the b110> direction, we have proposed that dimeric radicals play a key role for the bridge formation between the dangling bond rows with the space of two Si atoms on the (110) facet in order to enhance the lateral growth along these dangling bond rows (ledge formation [17]) by monomeric radicals [9,10]. We also proposed that the crystalline growth in the b110> direction is enhanced by the increased bridge formation on the (110) facet resulting from the increase of dimeric radicals in a gas phase.…”
Section: Discussionmentioning
confidence: 99%